Imagining the other and constructing Israelite identity in the Early Second Temple Period - Ben Zvi, Ehud 1951-; Edelman, Diana Vikander 1954- (London New Delhi New York Sydney Bloomsbury, 2014)
"This volume sheds light on how particular constructions of the 'Other'contributed to an ongoing process of defining what 'Israel' or an 'Israelite'was or was supposed to be in literature taken to be authoritative in the late Persian and Early Hellenistic periods. It asks, who is an insider and who an outsider? Are boundaries permeable? Are there different ideas expressed within individual books? What about constructions of the (partial) 'Other' from inside, e.g., women, people whose body did not fit social constructions of normalness? It includes chapters dealing with theoretical issues and case studies, and addresses similar issues from the perspective of groups in the late Second Temple period so as to shed light on processes of continuity and discontinuity on these matters. Preliminary forms of five of the contributions were presented in Thessaloniki in 2011 in the research programme, 'Production and Reception of Authoritative Books in the Persian and Hellenistic Period,' at the Annual Meeting of European Association of Biblical Studies (EABS)"--
"This volume sheds light on how particular constructions of the 'Other'contributed to an ongoing process of defining what 'Israel' or an 'Israelite'was or was supposed to be in literature taken to be authoritative in the late Persian and Early Hellenistic periods. It asks, who is an insider and who an outsider? Are boundaries permeable? Are there different ideas expressed within individual books? What about constructions of the (partial) 'Other' from inside, e.g., women, people whose body did not fit social constructions of normalness? It includes chapters dealing with theoretical issues and case studies, and addresses similar issues from the perspective of groups in the late Second Temple period so as to shed light on processes of continuity and discontinuity on these matters. Preliminary forms of five of the contributions were presented in Thessaloniki in 2011 in the research programme, 'Production and Reception of Authoritative Books in the Persian and Hellenistic Period,' at the Annual Meeting of European Association of Biblical Studies (EABS)"--
Machine generated contents note:. Introduction- Ehud Ben Zvi 2. Categorical Identities. 'Ethnified Otherness and Sameness' - a Tool for understanding Boundary Negotiation in the Pentateuch? - Kåre Berge / 3.Natives and Immigrants in the Social Imagination of the Holiness School - MarkBrett / 4. Gender and Identity in the Book of Numbers - Claudia V. Camp / 5. Womenon the Edge - Carey Walsh / 6. Disability, Identity, and Otherness in Post-ExilicIsraelite Thought - Rebecca Raphael / 7. Sex, Lies and Scrolls. The Invention ofCanaan in the Persian Period - Axel Knauf / 8. Imagined Community, ForgottenSpaces: The Others in the Report of Josiah's Reform (2 Kings 23) - TerjeStordalen / 9. Jonah and the Other: a Discourse on Interpretative Competence - SusanneGillmayr-Bucher / 10. Ruth, A Born-Again Israelite? One Woman's Journey ThroughSpace and Time - Anne-Mareike Wetter / 11. Overcoming Otherness in the Book of Ruth - RobertL. Cohn / 12. The Elusive Role of the Other in the Book of Esther - Orit Avnery / 13.The Other in Ezra-Nehemiah - Tamara C. Ezkenazi / 14. YHWH's 'Othering' of Israel- Diana V. Edelman / 15. Phinehas and the 'other' Priests in Ben Sira and 1Maccabees - Tobias Funke / 16. Otherized Bodies and Self Israelite Identity: AQumranic Perspective? - Anke Dorman / 17. Israelitization of the Other,Otherization of Judah / Israel and Matters of Social Memory - Ehud Ben Zvi / 18. TheOther: Sociological Perspectives in a Post-colonial Age - David Chalcraft.
Hier auch später erschienene, unveränderte Nachdrucke
Die eckig geklammerte Zählung steht auf dem Buchrücken
Keywords: Ethnicity in the Bible -- Congresses; Group Identity -- Congresses; Ethnoarchaeology -- Congresses; Jews -- Identity -- Congresses; Identity (Philosophical concept) -- Congresses; Konferenzschrift -- 2011 -- Thessaloniki; Aufsatzsammlung